The scholarship of teaching and learning in public administration: An agenda for future research - McDonald, Bruce D.; Hatcher, William; Bacot, Hunter; Evans, Michelle D.; McCandless, Sean A.; McDougle, Lindsey M.; Young, Sarah L.; Elliott, Ian C.; Emas, Rachel; Lu, Elaine Yi; Abbott, Michaela E.; Bearfield, Domonic A.; et al. (Journal of public affairs education : J-PAE., 2024)
Two essential questions for those leading the field of public administration are: What do we teach our students, and how do we train them? As scholars, we pay significant attention to our research, often to the detriment of recognizing the potential for merging our research with teaching through the Scholarship of Teaching and Learning (SoTL). However, given our students' leadership positions, SoTL-related work is vital to their success. In this article, we have come together to reflect on the state of SoTL's work in public administration. Through this reflection, we explore the windows of opportunity for research that we see emerging. Included among these opportunities is the need for research on how we can best serve students in and out of the classroom, as well as research the most effective way of managing our programs. We also see the need for research into faculty development, instructional design, and the return on investment for a public administration degree. Lastly, we argue for improved recognition of the value and contribution of SoTL-related work in tenure and promotion standards.